The Effect of Food Quality, Ewom, and Perceived Price on Revisit Intention at Scarlett’s Café Pantai Indah Kapuk Jakarta - Yuliantoro, Nonot; Sianipar, Rosianna; Hartono, Adeline; Liaw, Melvin (Jurnal Ekonomi, 2024)
This study is aimed to determine the effect of food quality, EWOM, and perceived price on the revisit intention of consumers at Scarlett's Cafe Pantai Indah Kapuk. The implementation of this research begins with theoretical exposure, distributing questionnaires, processing data, and analyzing data. The technique used for data collection is purposive sampling with the implementation of data collection using an online questionnaire instrument. Valid respondents were obtained as many as 196 out of 220 respondents who lived in Jabodetabek. Based on the results of data processing, the results show that perceived price has a positive and significant effect on revisit intentions, while food quality and EWOM do not have a positive and significant effect on consumer revisit intentions at Scarlett's Cafe Pantai Indah Kapuk. Food quality has no positive and significant effect due to the taste, texture, and color (appearance) of poor quality food when served. EWOM has no positive and significant effect because consumers are dissatisfied with the experience they get. So it is important to improve the quality of food so that consumers are satisfied and can provide a positive EWOM.